Developing RNAi pesticides in the post genomic era: A review - Duanmu, Haonan; Guo, Fangyuan; Liu, Ying; He, Kang (Advanced Agrochem, 2025)
RNA interference (RNAi) has emerged as a promising platform for next-generation pesticides, offering high target specificity and environmental safety. In the post-genomic era, rapid advances in insect genomics, delivery systems, and bioinformatics have significantly accelerated the development of RNAi-based pest control strategies. This review summarizes current progress in RNAi mechanism elucidation, target gene selection, and delivery approaches including host-induced gene silencing (HIGS), spray-induced gene silencing (SIGS), and virus-induced gene silencing (VIGS). Key challenges—such as interspecies variability in RNAi efficiency, dsRNA degradation, and off-target effects—are discussed in detail. Machine learning (ML) and genome-wide screening play a critical role in optimizing siRNA design and reducing ecological risks. Commercial products such as Ledprona and MON87411 maize exemplify the practical potential of RNAi-based pesticides. Future success will depend on integrating comparative genomics, ML-based off-target prediction, and ecological risk assessment frameworks to ensure safety and sustainability in applications.